MONITORING OF THE BEARING CAPACITY OF BRIDGE STRUCTURES DURING OPERATION - MONZHERAN, DMYTRO; SIKORSKYI, OLEKSІI; KOVALENKO, YURII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper presents the results of monitoring the durability of elements of bridge concrete structures and assessing their operational duration. Precast concrete structures simplify the processes of constructing complex transport infrastructure facilities. Monitoring the durability of such facilities is complicated due to the need to use destructive analysis methods. Existing high-precision analysis methods require complete destruction of samples. The paper uses non-destructive analysis methods. Methods for determining the compressive strength of standardized cores and a method for determining aggressive effects by detecting carbonization processes were used. Monitoring is carried out in the early stages of the facility's operation. The study used standardized cores of small and large sizes. The nature of the destruction complies with the norms of state standards, and the determined average strength is not less than the passport value. Determination of the possible onset of chemical carbonization processes using the phenol-phthalein identification method showed the absence of carbonization processes. At the early stage of monitoring, it is difficult to predict the remaining period of operation, which is why the feasibility of comprehensive monitoring, two or more research methods is significant. The “stress-strain” loading methodology was used to compare the obtained values of strength coefficients to those specified in the standards. The deformation coefficient (εcu,θ), the calculated indicator for θ = 20 °C according to regulatory documents, is 2.5. The design indicator εcu,θ=25 is 3.13. The core study showed that during the operation period, the strength indicators remain within the design grade of concrete C25/30, respectively, the average values are 27.7 ... 29.6 MPa. The use of methyl-phthalein indicator indicates the absence of carbonization corrosion processes.
Keywords: concrete; binder; non-destructive analysis methods; durability; leaching; monitoring